Effect of ball milling and iron mixing on structural and morphological properties of magnesium for hydrogen storage application. (2021) - Rattan Paul, Devina; Sharma, Anshu; Panchal, Priyanka; Chaudhary, Sudesh; Patidar, D.; Nehra, S.P.
Abstract: Being a clean energy carrier, hydrogen is considered as fuel for future. It is the lightest and most abundant element in the universe. Magnesium has shown promise for onboard hydrogen storage as it has enormous hydrogen content. Further, uptake of molecular hydrogen in modified Mg is a prospect for efficient hydrogen storage. Hydrogen uptake capacity of Mg can be improved with loading of transition metals. In this work effect of the ball-milling and different wt% of Fe on structural and morphological properties of Mg powder was conducted. Pristine Mg powder was milled for 12 h and then milled for a further 2 h after adding x wt% of Fe (x = 5, 10 & 20). In this manner Mg - x wt% Fe (x = 5, 10 & 20) nanocomposites were prepared. Structural, morphological and elemental analysis of these samples is completed by X-ray diffraction (XRD) and field emission scanning electron microscope (FE-SEM) and energy-dispersive X-ray spectroscopy (EDXS) respectively. Results indicate that the Mg with an effective additive could be used as hydrogen storage material systems.